PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS VII SMP NEGERI 1 BATANG KUIS TAHUN PEMBELAJARAN 2021-2022 - Rahajeng Pratiwi; Mimi Rosadi (Jurnal Inovasi Penelitian, 2023)
This study aims to determine the ability of students' learning outcomes before using the picture and picture model on the ability to write poetry by students and to determine the effect of the picture and picture model on the poetry writing ability of class VII students of SMP Negeri 1 Batang Kuis. This research is a quantitative study using a quasi-experimental method with the type of One Group Pretest-Postest (single group initial test-final test). The subjects of this study were 20 students of class VII SMP Negeri 1 Batang Quiz, consisting of 10 male students and 10 female students. From the results of the pre-test, it can be seen that 16 students (80%) did not complete, only 4 students (20%) completed with an average score of 66.5. The application of the picture and picture model with media images has an effect on increasing student activity in learning poetry writing skills. In post-test I, there were 12 students who completed (60%) with an average score of 74.5 and as many as 8 students (40%) who had not completed. In post-test II, there were 19 students who passed (95%) with satisfactory scores and met the Minimum Completeness Criteria (KKM) requirements, with an average score of 87. Only 1 student (5%) did not complete. From these results it can be seen that the use of the Picture and Picture learning model has an effect on students' ability to write poetry.